The Role of The Mandailing Community In Supporting Islamic Economic Independence in Medan Society - Mhd Zulkifli Hasibuan; Bayu Wulandari; Muhammad Hilman Fikri; Dahrul Siregar (UPT Publikasi Ilmiah UNISBA, 2026)
This study explores the role of the Mandailing community in Medan in supporting the Islamic economy through ethical and sustainable sharia-based practices. Using a qualitative approach, the study involved 35 informants from various backgrounds to explore their understanding, involvement, and challenges in implementing sharia economic principles. The results indicate that the Mandailing community has a high level of acceptance of sharia values, solidarity, and kinship relations, which serve as a social network that supports business management. Education and training focused on sharia financial literacy have proven effective in increasing understanding and trust in sharia financing products. However, limited access to sharia financial institutions remains a major obstacle to the growth of Micro, Small, and Medium Enterprises (MSMEs). This study emphasizes the need for collaboration between the government and financial institutions to improve access to financing and demonstrates that a sharia-based economic approach among the Mandailing community can create equitable and sustainable prosperity.